Analisis Butir Soal Ulangan Harian Siswa Mata Pelajaran PPKn Kelas IV Menggunakan Rach Model di Madrasah Ibtidaiyah Negeri - Rifana, Fitria; Ramadhan, Syahrul; Putro, Khamim Zarkasih (Institut Agama Islam Daruttaqwa Gresik, 2024)
The study aimed to analyze the items on students' daily test questions on PPKN subjects made by the teacher to measure learning outcomes during the previous lesson process. Conducted on fourth-grade students at the 01 West Pasaman State Madrasah Ibtidayah. The method used in this research is descriptive quantitative using Rasch model data analysis with Win Step software. The results of the data analysis carried out were on the reliability data analysis using Winstep Cronbach Alpha 0.49 software. From the existing data, it is clear that the level of reliability of the questions is still relatively weak. The results of the Rasch model of person reliability and item reliability are 0.47 and 0.52. The results of the analysis of the quality of the items in terms of the validity of the items using the Rasch model obtained 6 questions that were said to be valid and 24 questions that were said to be invalid because they did not meet the requirements for the MNSQ outfit, ZSTD outfit, and the Point Measure correlation (PT measure Corr). In using the Rasch model it is felt to be more accurate because it meets these three criteria, so it is considered valid. above the P value or the level of difficulty of the items below 0.25, there are 3 items, meaning the item is very difficult. Questions that are above 0.75 have 5 items meaning the question is too easy. And questions that are scored between 0.25-0.75 have 17 questions. That is, 18 questions have a good level of difficulty. Analysis of distracting items using the Winstep Rasch Model software for 25 daily test questions for students of Civics class IV at Madrasah Ibtidayah Negeri 01 Pasaman Barat shows that there are 23 questions with good functioning distractors. Items where the distractor does not function properly are 5 questions.